Mediational Effect of Fairburn’s Transdiagnostic Mechanisms Between Attachment to the Mother and Eating Disorder Symptoms in a Clinical Sample - Cortés-García, Laura; Martínez Calvo, Carmen; Senra, Carmen (Frontiers in Psychology, 2022)
Objective Research has supported a link between insecure attachment and eating disorders (EDs); however, little is known about how this influence is exerted in young female EDs patients. This study tested, for the first time, a multiple mediational model, wherein the four Fairburn’s transdiagnostic mechanisms mediated the relationship between attachment to the mother and ED symptoms. Methods A total of 101 female young EDs patients aged 15–24 were administered the Inventory of Parent and Peer Attachment, Eating Disorder Inventory-3 and Eating Attitudes Test-26 to assess attachment, the four transdiagnostic maintaining mechanisms and ED symptoms, respectively. Results Comparison analyses showed that there were no significant differences between the diagnostic groups in terms of attachment and the transdiagnostic variables. Multiple mediational analyses indicated that low self-esteem and clinical perfectionism were significant mediators between insecure attachment to the mother and ED symptoms, while controlling for depressive symptoms. Conclusion These findings suggest that the distal risk influence of insecure attachment to the mother in the development of ED symptoms might be explained by low self-esteem and high clinical perfectionism, controlling for depressive symptoms. Further investigation into the efficacy of cognitive-behavioral treatments targeting insecure attachment representations for young EDs patients is recommended.